2022
DOI: 10.3389/fonc.2022.852952
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo miRNA Decoy Screen Reveals miR-124a as a Suppressor of Melanoma Metastasis

Abstract: Melanoma is a highly prevalent cancer with an increasing incidence worldwide and high metastatic potential. Brain metastasis is a major complication of the disease, as more than 50% of metastatic melanoma patients eventually develop intracranial disease. MicroRNAs (miRNAs) have been found to play an important role in the tumorigenicity of different cancers and have potential as markers of disease outcome. Identification of relevant miRNAs has generally stemmed from miRNA profiling studies of cells or tissues, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…We found that FFPE-CUTAC sensitively detects cCRE clusters spanning microRNA loci that gain RNAPII in the RELA fusion-driven tumor. Strikingly, the 10 most down-regulated cCREs corresponded to two unlinked loci for the mouse Mir124a microRNA, which was previously described as a neuronal differentiation factor 61 , a tumor suppressor in brain 62 and a unique human biomarker for H. pylori infection and gastric cancer risk 53 . Although Mir124a is one of the most abundantly expressed microRNAs in the central nervous system 61 , we found that it is present at only average levels in RNA-seq data.…”
Section: Discussionmentioning
confidence: 91%
“…We found that FFPE-CUTAC sensitively detects cCRE clusters spanning microRNA loci that gain RNAPII in the RELA fusion-driven tumor. Strikingly, the 10 most down-regulated cCREs corresponded to two unlinked loci for the mouse Mir124a microRNA, which was previously described as a neuronal differentiation factor 61 , a tumor suppressor in brain 62 and a unique human biomarker for H. pylori infection and gastric cancer risk 53 . Although Mir124a is one of the most abundantly expressed microRNAs in the central nervous system 61 , we found that it is present at only average levels in RNA-seq data.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, microRNA-146a was shown to suppress melanoma metastatic activity in brain metastasis [ 122 ], while miR-124a, a miRNA that is highly expressed in the brain was shown as a suppressor of melanoma metastasis in vivo, particularly of brain metastasis. A significant fraction of melanomas that metastasized to the brain was found to carry a decoy of miR-124a [ 123 ]. MicroRNA-23a was shown to inhibit melanoma cell proliferation, migration, and invasion in mice through a negative feedback regulation of sdcbp and the mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) signaling pathway [ 124 ].…”
Section: Extravasation Of Tumor Cells Through the Blood–brain Barrier...mentioning
confidence: 99%